Clinical Application of Mesenchymal Stem Cells and Novel Supportive Therapies for Oral Bone Regeneration. (12th May 2015) - Padial-Molina, Miguel; O'Valle, Francisco; Lanis, Alejandro; Mesa, Francisco; Dohan Ehrenfest, David M.; Wang, Hom-Lay; Galindo-Moreno, Pablo
Abstract : Bone regeneration is often needed prior to dental implant treatment due to the lack of adequate quantity and quality of the bone after infectious diseases, trauma, tumor, or congenital conditions. In these situations, cell transplantation technologies may help to overcome the limitations of autografts, xenografts, allografts, and alloplastic materials. A database search was conducted to include human clinical trials (randomized or controlled) and case reports/series describing the clinical use of mesenchymal stem cells (MSCs) in the oral cavity for bone regeneration only specifically excluding periodontal regeneration. Additionally, novel advances in related technologies are also described. 190 records were identified. 51 articles were selected for full-text assessment, and only 28 met the inclusion criteria: 9 case series, 10 case reports, and 9 randomized controlled clinical trials. Collectively, they evaluate the use of MSCs in a total of 290 patients in 342 interventions. The current published literature is very diverse in methodology and measurement of outcomes. Moreover, the clinical significance is limited. Therefore, the use of these techniques should be further studied in more challenging clinical scenarios with well-designed and standardized RCTs, potentially in combination with new scaffolding techniques and bioactive molecules to improve the final outcomes.